Compreensão de nutricionistas da alimentação escolar sobre educação alimentar e nutricional - Soares, Gabriela Benevides (2015)
Food and nutrition education (EAN) has undergone conceptual and methodological changes over the past decades. Under the school feeding, the EAN is one of the national program of action axes School Feeding (PNAE), and competence of the nutritionist coordinate and perform these actions together with the school actors in a context where are continuous, permanent, problem-solving and cross. The objective of this study was to understanding the nutritionists of the National School Feeding Programme on food and nutrition education. It is a descriptive exploratory study through interviews with 50 nutritionists school feeding of the five Brazilian regions. Data were collected on site from March to November 2013 using a semi-structured open questions. Nutritionists were asked about their understanding of food and nutrition education, its role in carrying out these actions and what factors motivate and hinder the development of the EAN of shares in the PNAE. Data analysis was performed using the collective subject discourse technique (DSC), starting from the raw speech, which were removed from the key expressions and later the central ideas (CI). From the IC who shared the same elements under discussion, these were grouped into categories that later composed the DSC. Four issues have been analyzed, and each was chosen the speech which represented the largest share of core ideas. As for the understanding of the EAN lines they showed that nutritionists interviewed see as a process of teaching and learning about food, and its role teaching about food and nutrition. The most motivating factor shared the responses was the need to form healthy eating habits. While recognizing the need for continuity in multiplier training activities, the realization of EAN is conditional upon the presence of a nutritionist. This may explain the higher difficulty reported for their achievement in the school environment, which is the lack of time and / or professionals in sufficient numbers in the technical framework. The shy recognizing the need for coordination and continuity of actions in the speeches allows us to understand the EAN under the school feeding as a complex process that involves all social spheres of the individual insertion.